Dental Based Neurological Disorders Prediction Using Deep Learning Techniques - et. al., N.Valarmathi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Dental diseases based on neurological disorders arises as people gets older. It may also cause tooth decay and losing of tooth. People with poor oral health can also experience this kind of diseases. So we are developing a tool where we can predict the diseases and can take the necessary steps in the early stage. It is important for one to keep their dental a perfect one. Once they loss it their confidence automatically gets decreased. Hence by developing this people can get rid of the problems and can also avoid dental based neurological problems. Since the development of technology is in rapid speed it is necessary to upgrade our current technologies with some advanced features. In this project we will be collecting the images of the dental and feed it as the input. From that the feature values will be collected and classify them into the diseases. It uses Convolutional Neural Network (CNN) algorithm where the diseases can be classified using this algorithm. The development of this project can help people to find the diseases just by scanning their dental part. It makes the prediction to be a simple process so that the dentist itself can use this and find the disorders. From this project we can conclude that it is simple that a neurological disorder that is caused by dental can be predicted easily and hence preventing them.